The Incidence and Treatment of Cerebrospinal Fluid Leakage Following Repair of Congenital Spinal Pathologies - Shakeel Ahmed, Saqib Khalil, Shoaib Saleem Khan, Badar Uddin Ujjan, Mian Ayaz Ul Haq, Waqas Noor Chughtai, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The study's goal is to find out how often individuals with myelomeningocele and TCS repair have leakage of cerebrospinal fluid. Study Design: Cross-sectional Place and Duration: Women medical college Abbottabad and Children hospital and the institute of child health, Multan, during from the period July, 2021 to Dec, 2021. Methods: There were 55 participants of both sexes in this research. Those being treated ranged in age from 5 to 20 years old. After obtaining written permission, we collected demographic data on each patient, including their age, gender, and BMI measurements. There were patients who had TCS repair as well as those who had undergone myelomeningocele repair procedures. It was determined how often cerebrospinal fluid leaks occurred in patients. SPSS 22.0 was used to analyze all of the data. Results: Among 55 cases, majority were males 32 (58.2%) and 23 (41.8%) were females. Included patients had mean age 9.5±6.14 years. Frequency of CSF leak was found among 18 (32.7%) patients. The mean duration of CSF leaks was 13.11±10.34 days. In 18 patients of CSF leaks, Frequency of MMC repair was 11, TCS release was found in 3 patients and meningocele repair in 4 patients. With the use of tincture benzoyl-enhanced primary wound healing in three patients with CSF leaks during surgery, the HCP postoperative signs were resolved. HCP was found in two further patients after their sutures mended with benzoyl tinctures, and they were placed in the shunt. Conclusion: In this research, we found that CSF leaks are more common in patients having myelomeningocele and TCS repair. Skin-healing tincture benzoyl will help these people. Keywords: Cerebrospinal fluid leak (CSF), Tether cord syndrome (TCS), Myelomeningocele (MMC)